Prevalence of Selected Chronic Non-Communicable Diseases in Nepal - Dhimal, Meghnath; Karki, Khem Bahadur; Sharma, Sanjib Kumar; Aryal, Krishna Kumar; Shrestha, Namuna; Poudyal, Anil; Mahato, Namra Kumar; Karakheti, Ashwin; Sijapati, Milesh Jung; Khanal, Puspa Raj; Mehata, Suresh; Vaidya, Abhinav; et al. (Journal of Nepal Health Research Council, 2019)
Background: The burden of non-communicable diseases has increased in the last few decades in low-and middle-income countries including in Nepal. There is limited data on population based prevalence of non-communicable diseases. Hence, this study aims to determine the nationwide prevalence of selected chronic non-communicable diseases in Nepal. Methods: A nationwide cross-sectional population-based study was conducted from 2016 to 2018. Data was collected electronically on android device inbuilt with research and monitoring software from 13200 eligible participants aged 20 years and above. Data was cleaned in SPSS version 20.0 and analyzed using Stata version 13.1. Results: The overall prevalence of selected non-communicable diseases was found to be chronic obstructive pulmonary disease 11.7% (95% CI: 10.5-12.9), diabetes mellitus 8.5% (95% CI: 7.8-9.3), chronic kidney disease 6.0% (95% CI: 5.5-6.6) and coronary artery disease 2.9% (95% CI: 2.4-3.4) in Nepal. Prevalence of non-communicable diseases varied across provinces. Higher prevalence of chronic obstructive pulmonary disease (25.1%, 95% CI: 18.1-33.8) in Karnali Province, diabetes (11.5%, 95% CI: 9.8-13.4) in Province 3, chronic kidney disease (6.8%, 95% CI: 5.6-8.1) in Gandaki Province and coronary artery disease in Gandaki (3.6%, 95% CI: 2.2-5.7) and Sudurpaschim Province (3.6%, 95% CI: 2.1-6.1) was observed. Conclusions: The study reported substantial proportion of adult population was found to have chronic non-communicable diseases in Nepal. The findings of this study may be useful for revising/updating multi-sectoral action plans on prevention and control of non-communicable diseases in Nepal. Keywords: Chronic kidney disease; chronic obstructive pulmonary disease; coronary artery disease; diabetes mellitus; non-communicable disease.